Bio-Inspired C/N/TiO2 Hybrid Composite Heterostructure: Enhanced Photocatalytic Activity under Visible Light. (16th September 2022) - Gandi, Shyam Sundar; Gandi, Suman; Parne, Saidi Reddy; Lakavat, Motilal; Lakkimsetty, Nageswara Rao; Gedda, Gangaraju
Abstract : The hydrothermal treatment was used to create a natural hierarchical bio-inspired carbon and nitrogen-doped C/N/TiO2 hybrid composite. It is the goal of this work to investigate the photocatalytic activity of bio-inspired C/N/TiO2 hybrid composite. Techniques such as X-ray powder diffraction, scanning electron microscopy, UV-Vis absorption spectroscopy, FTIR, Raman, and photoluminescence spectroscopy were used to explore the structural, morphological, and photocatalysis characteristics of the bio-inspired C/N/TiO2 hybrid composite. By doping carbon and nitrogen, TiO2 nanotubes were able to improve the photocatalyst properties of the C/N/TiO2 hybrid composite, decrease the energy band gap (∼2.55 eV), and result in increased electron transfer efficiency when compared to pure TiO2 . The photocatalytic degradation of pollutants (rhodamine B (RhB)) is made possible by the use of a bio-inspired C/N/TiO2 hybrid composite that has high interconnectivity and an easily accessible surface.